2015
DOI: 10.1371/journal.pntd.0003785
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Progress towards the Elimination of Gambiense Human African Trypanosomiasis

Abstract: BackgroundOver the last few years, momentum has gathered around the feasibility and opportunity of eliminating gambiense human African trypanosomiasis (g-HAT). Under the leadership of the World Health Organization (WHO), a large coalition of stakeholders is now committed to achieving this goal. A roadmap has been laid out, and indicators and milestones have been defined to monitor the progress of the elimination of g-HAT as a public health problem by 2020. Subsequently, a more ambitious objective was set for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 18 publications
1
114
0
1
Order By: Relevance
“…In recent years, great improvements to curative drugs and screening programmes have contributed to a substantial decline in disease incidence [1]. In addition, advances in tsetse control have meant that control programmes can use strategies with interventions against both the parasite and vector [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great improvements to curative drugs and screening programmes have contributed to a substantial decline in disease incidence [1]. In addition, advances in tsetse control have meant that control programmes can use strategies with interventions against both the parasite and vector [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…, spread by tsetse fly vectors (genus Glossina ). The disease is endemic in foci in sub-Saharan Africa [1, 2]. After a peak of infection in the 1990s, the incidence of HAT has considerably declined in recent years [1].…”
Section: Introductionmentioning
confidence: 99%
“…The disease is endemic in foci in sub-Saharan Africa [1, 2]. After a peak of infection in the 1990s, the incidence of HAT has considerably declined in recent years [1]. It is estimated, however, that a significant number of new cases remain unreported or undiagnosed [35].…”
Section: Introductionmentioning
confidence: 99%
“…The first report monitoring the progress of the gambiense elimination campaign indicated that the program was on track, with a progressive decrease in the number of cases reported over the two time periods studied and a 57% reduction in the population classified at high or very high risk of gambiense HAT [9]. Although progress has been made in achieving the goal of eliminating gambiense HAT as a public health problem by 2020, many challenges still lie ahead.…”
Section: Prospects For Controlmentioning
confidence: 99%